A journey of hope: a primigravida with an ovarian teratoma - Samsudin, Suhaiza; Alias, Norasikin; Che Yusof, Mohd Daud; MA, Fatin ‘Amira (UniKL Royal College of Medicine Perak (UniKL RCMP) Managed by P.C.M. SDN. BHD, 2024)
Ovarian teratomas (OTs) are categorized as either mature or immature. Mature cystic teratomas (MCTs), also known as dermoid cysts, are the most common type of germ cell tumours in the ovaries of women of reproductive age. OTs generally remain asymptomatic until they reach a substantial size. Transvaginal and transabdominal ultrasounds are crucial for evaluating pelvic masses and distinguishing between benign and malignant cases. These imaging methods are commonly used for diagnosis. A histopathology report is essential for confirming an OT diagnosis, and surgical intervention, using various approaches, is the only treatment option. In this case, we reported a primigravida woman at 8 weeks of gestation presented with irregular menses and ultrasound imaging revealed a unilateral dermoid cyst, which was subsequently diagnosed as a mature ovarian teratoma.